Factors affecting the library usage patterns of the undergraduate students of the UP College of Architecture - Galora, Huwaran Mapalarin Sinag C. (2006)
Students experience and use the college library. Their perceptions and assessment regarding the improvements of the college library are two factors that must be recognized as a gauge of determining the efficiency of its services. That is why the students are chosen in this study as respondents to be able to help in assessing the college library of the UP College of Architecture. The study attempted to determine the library usage patterns of UP College of Architecture students. Specifically, it sought to know the factors that influence their library usage patterns. It also aimed to know their evaluation of the library's resources, facilities and services. Lastly, it sought to show the significant relationship between the library resources, facilities and services, and the library usage patterns of the architecture students.